AD, Volume 20, n° 1, 1995 - Full Issue - Journal System, (Africa Development, 1995)
Contents Ajustement structurel et développement en Afrique : L'expérience des années 80 Armand Gilbert Noula ................................ 5 Feminism or Femocracy? State Feminism and Democratisation in Nigeria Amina Mama ................................... 37 Manioc, rente foncière et situation des femmes dans les environs de «Kpove-Village» en pays Ouatchi Ewihn-Liba Pana ................................. 59 Differential Socio-economic Impact of Food Shortages and Household Coping Strategies: A Case Study of Wolaita District in Southern Ethiopia Dagnew Eshete ...................................... 89 Spatial Mismatch Between Population Density and Land Potential: The Case of Zimbabwe Assefa Mehretu ........................................ 125 Book Reviews Beyond Communal Wisdom:Land in African Agrarian Systems by Thomas J. Bassett and Donald E. Crummey; Cattle, Capitalism and Class: Ilparakuyo Maasi and Transformations by Peter Rigby Paul Tiyambe Zeleza .................................. 147 A la croisée de la crise des universités en Afrique Charles Z. Bowao ................................... 159 Determinants of Fertility and Child Mortality in Côte d'Ivoire and Ghana(LSMS Working Paper No. 103) by Kofi D. Benefo and T. Paul Shultz Babatunde A. Ahonsi .................................... 165 Publications received ..................................... 169